2022
DOI: 10.3390/agronomy12061412
|View full text |Cite
|
Sign up to set email alerts
|

Soybean Yield Response of Biochar-Regulated Soil Properties and Root Growth Strategy

Abstract: Continuous cropping obstacles limit soybean production. Biochar is beneficial for soybean growth, but it is unclear whether biochar performs a sustainable role in continuous cropping. To further explore the effects of biochar on soil properties and soybean growth, a ceramic Wagner pot-simulated field experiment was conducted with biochar at different doses (12, 24, and 48 t·ha−1) over a period of 3 years, no fertilizer, no biochar (CK) and fertilizer (F)treatments were used for comparison. The results showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…Moreover, biochar is alkaline and can increase the availability of soil nutrients and facilitate crop nutrient uptake 33 . In addition, our previous studies have found that biochar application can increase effective soil nutrient content, improve continuous cropping soil pH and stimulate root growth and development 34 . This may enhance nutrient and water transport from roots to aboveground parts, ultimately increasing soybean leaf area and LAI.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, biochar is alkaline and can increase the availability of soil nutrients and facilitate crop nutrient uptake 33 . In addition, our previous studies have found that biochar application can increase effective soil nutrient content, improve continuous cropping soil pH and stimulate root growth and development 34 . This may enhance nutrient and water transport from roots to aboveground parts, ultimately increasing soybean leaf area and LAI.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, BCAF was able to boost soybean output even in situations where fertilization was reduced by 50%. This primarily is explained by the possibility that applying fertilizer and biochar together could improve soil nutrient availability, raise soil nutrient content, and improve fertilizer utilization, thus providing adequate and effective nutrient supply for soybean growth and yield formation 34,48 . This would result in an adequate and efficient supply of nutrients for soybean development and yield creation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, the resulting biochar is a solid carbonaceous material with high aromatization, good stability, large specific surface area, rich pore structure, and strong adsorption capacity. It is widely used to improve soil fertility [ 41 , 42 ] and overcome obstacles for continuous cropping [ 43 , 44 ], and as a cost-effective adsorbent for sewage treatment [ 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%